Backup Plans: The Impact of Disclosure on Perceptions of Expert Competence - Palmeira, Mauricio; Polman, Evan (Management Science, 2025)
People often consult experts to provide solutions to their problems. Oftentimes, an initial attempt to solve a problem fails, and these experts (e.g., advisors, consultants, specialists, and service providers) will resort to a backup plan. A backup plan can be presented when it is needed (i.e., after an initial failure) or in advance (i.e., before a potential failure). We examine how the timing of disclosure of a backup plan affects judgments of an expert’s competence. We show that although people expect experts to have a backup plan, they react more negatively if it is presented after (versus before) it is needed, all things equal. This “competence penalty” disappears when people are prompted to think about what an expert would do in case of failure as indeed, an alternative plan is expected. Importantly, our findings indicate that there is no competence penalty for early disclosure of a backup plan, regardless of the outcome of the initial plan: if it has failed, has succeeded, or is still ongoing. However, we do find one exception; early disclosure has a negative impact if multiple backup plans are disclosed while the initial plan is in progress. This paper was accepted by Jack Soll, behavioral economics and decision analysis. Funding: Funding for all studies was provided by the MUMA College of Business, University of South Florida. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2023.02615 .